(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The Bologna Process for the creation of a barrier-free European Higher Education Area was initiated almost 18 years ago on 19 June 1999 in a joint declaration by Europe’s education ministers. Originally, thirty countries affirmed their commitment to this goal and began the task of facilitating mutual access to science and education resources as well as improving the international dialogue and the mobility and exchange of students, teachers and researchers. Problem statement. In the meantime, the group of countries participating in the Bologna Process has grown continuously. The 48th and latest country to be included in the European Higher Education Area and hence also in the Bologna Process was the Republic of Belarus. That was here in Yerevan two years ago at the Ministerial Conference. The meeting was dominated by the challenges of the economic and social crisis confronting numerous European countries at that time, the consequences of which we can still observe today in manifold ways. In the course of these developments, separatist voices have gained noticeably in influence for the first time. That is why it was all the more important that a positive example of Europe as a place for academic freedom was renewed and underlined in the Yerevan Communiqué: Short analysis of current researches. “We will support higher education institutions in enhancing their efforts to promote intercultural understanding, critical thinking, political and religious tolerance, gender equality, and democratic and civil values, in order to strengthen European and global citizenship and lay the foundations for inclusive societies.” [5] The ideal of the Bologna Process is thus embedded in a concept of European and global citizenship that is based on the enlightened values of democracy and human rights. We are hence not talking here about the technicistic realization of harmonization measures in higher education, particularly in the administration and organization of degree programmes. The Bologna Process is closely linked to the development of inclusive societies, that is, “societies for all”, where social, economic and political participation is not delimited by categories such as race, gender, class, generation or origin. The measures anchored in the Bologna Process are oriented towards this guiding principle of critical and independent thinking, of inclusion and equality at national as well as international level. This is the benchmark against which the Bologna reforms must be measured. Research novelty. Criticism of the ways in which the Bologna reforms are implemented and standardized must therefore always also take into account this dimension of global politics alongside academic aspects and higher education policies. However, legitimate political claims must not be fulfilled to the detriment of scientific freedom. The danger is inherent in the very structure of the Bologna Process that scientific freedom in the different member countries will be levelled out in favour of the international harmonization wanted at political level. If it wants to avoid shipwreck, European higher education policy must navigate skilfully between these two poles, the seductive Scylla of scientific freedom and the shapeless Charybdis of levelled local and regional peculiarities. My hypothesis is that the harmonization process in the European Higher Education Area can even hinder student mobility if it is put into practice badly. I would like to illustrate this using data gathered in the framework of a research project at Heinrich Heine University Düsseldorf in which software for planning overlap-free degree programmes has been developed. My question is: How can international mobility be implemented in a targeted manner and put into practice at the level of programme planning and curriculum development?